Ritual Nyonteng Kolbuk sebagai Representasi Harmoni Kultural - Prayogi, Dini Siamika Tito (Koordinatorat Perguruan Tinggi Keagamaan Islam Swasta Wilayah IV Surabaya, 2025)
This research discusses the Nyonteng Kolbuk Ritual, a tradition of caring for springs in Sumberwringin, Bondowoso, as a representation of harmony between humans, nature, and God, employing the semiotic approaches of Peirce and Barthes. This research aims to uncover the symbolic meaning of the signs in this ritual and to interpret the meaning of myths and ideological messages relevant to local cultural harmony and global relevance. The method of data collection involves observation, interview, and documentary research. Ritual symbols, such as water, goat's head offerings, a bridal couple, and agricultural products, are analyzed based on their iconic, indexical, symbolic, and ideological meanings. The results show that this ritual reflects local wisdom values ​​such as ecological awareness, spirituality, social solidarity, and cultural preservation. Water symbolizes the purity and balance of the cosmos, the goat's head represents sacrifice and gratitude, and the bridal couple, along with the agricultural products, signify ecological justice. Overall, Nyonteng Kolbuk is a sign system rich with moral, spiritual, and ecological values, emphasizing the importance of cultural harmony for the sustainability of communal life.